The Effectiveness of Images in Improving the Writing Skills of Students of Darul Ulum 2 High School in Jombang, East Java: فعالية الصور لترقية كتابة تلاميذ المدرسة الثانوية دار العلوم 2 بجومبانج جاوة الشرقية - Ahmad Faisol Qohar; A. Halil Thahir; Mokhammad Miftakhul Huda (Journal of Arabic Language Teaching, 2021)
Learning Media is one of the essential elements in the teaching and learning process to achieve the goals aspired. Learning Media develops along with the development of science and technology. This is also true in learning writing skills. Writing skills are the most difficult of the four language skills. Therefore, it requires selecting appropriate media and being used effectively to achieve the purpose of learning writing skills. In this study, researchers tried to use image media to improve students ' writing skills. The purpose of this study was to determine (1) the use of image media to improve the writing skills of the student of SMA Darul Ulum 2 Unggulan BPPT Jombang and (2) the effectiveness of the use of image media to improve the writing skills of the student of SMA Darul Ulum 2 Unggulan BPPT Jombang. This study is quantitative research with experimental methods, using three data collection methods: observation, interview, and test. At the same time, data analysis is done in three steps, namely data preparation, data presentation, and conclusion. The results of this study are (1) the teaching and learning process by using image media to improve the writing skills of the student of SMA Darul Ulum 2 Unggulan BPPT Jombang consists of six steps, namely presenting material, image recognition, distributing images, asking students to make essays based on images, giving opportunities to ask students, and closing learning activities. (2) the result of the significance test is 0.000, and this result is smaller than 0.05. So that Ho rejected and Ha accepted, it can be interpreted that the image effectively improves the students' writing skills of SMA Darul Ulum 2 Unggulan BPPT Jombang. الوسائل التعليمية إحدى العناصر المهمة في عملية التعليم للحصول على الأهداف المرجوة، وهي تطورت مع تطور المعلومات والتكنولوجيا. وكذلك في تعليم مهارة الكتابة، فالكتابة أعلى المهارات من مهارة اللغة الأربعة. فلذلك يحتاج إلى اختيار الوسائل المناسبة واستخدامها على نحو الفعال لتكون الأهداف المرجوة فيه محصولة بالتمام. في هذا البحث يجرب الباحث استخدام الوسائل الصور لترقية كفاءة الطلاب في مهارة الكتابة. والأهداف من هذا البحث لمعرفة (1) استخدام وسائل الصور لترقية مهاوة الكتابة لتلاميذ المدرسة الثانوية دار العلوم 2 المتميزة جومبانج ، (2) فعالية استخدام وسائل الصور لترقية مهارة الكتابة لتلاميذ المدرسة الثانوية دار العلوم 2 المتميزة جومبانج. وهذا البحث بحث كمي بالمنهج التجريبي. ويستخدم ثلاث طرق جمع البيانات وهي الملاحظة والمقابلة والاختبار، وأما تحليل البيانات على ثلاث خطوات من إعداد و تقديم واتنتاج. ونتيجة هذا البحث (1) تتكون عملية التعليم باستخدام وسائل الصور لترقية مهارة الكتابة لتلاميذ المدرسة الثانوية دار العلوم 2 المتميزة جومبانج على ست خطوات، وهي تقديم الباحث على المواد التعليمية، وتعريف عن الصور، و يوزع الصور على التلاميذ، يأمر الباحث التلاميذ ليكتب الإنشاء بصور المسلسلة، يعطي الباحث فرصة للسؤال، يختم الباحث المادة بخلاصة التدريس و الدعاء و السلام، (2) ونتيجة اختبار الأهمية 0،000، وهذه النتيجة أقل من 0،05. إذا الفرضية الصفرية مردودة والفرضية العملية مقبولة، بمعنى أن وسائل الصور فعال لترقية مهارة الكتابة لتلاميذ المدرسة الثانوية دار العلوم 2 المتميزة جومبانج.